The Driving and Restraining Factors for Peat Forest Park Management and Sustainable Development Goal Partnership: A Case Study of the Orang Kayo Hitam Forest Park, Province of Jambi, Indonesia - Christine Wulandari; Novriyanti Novriyanti; Dian Iswandaru (The Indonesian Forestry Certification Cooperation, 2021)
Indonesia has the second largest peatland area in the world, of which 19% is damaged due partly to forest fires and encroachment. The Orang Kayo Hitam (OKH) forest park located in the Indonesian province of Jambi is one among several peat forests in the country that remain largely intake. But as do other forested areas, the park faces severe encroachment threats. Multistakeholder partnership as stipulated by Sustainable Development Goals (SDG) 17 offers a reasonable strategy to mitigate the threats. This article studies the driving and restraining factors, both externally and internally, that affect preservation of the park’s peatland as well as the development of effective partnership strategies. Results of the force field analysis show that community’s knowledge and awareness about the link between the park’s ecological and economic functions are the strongest internal driving factors, while lack of them are the strongest restraining ones. Availability of endemic species and frequency of forest fires are the strongest external driving and restraining factors, respectively.